Effect of Aloe Vera and Pantoprazole on Gastroesophageal Reflux Symptoms in Mustard Gas Victims: A Randomized Controlled Trial - Yunes Panahi, Jafar Aslani, Ali Hajihashemi, Mahdieh Kalkhorani, Mostafa Ghanei, Amirhossein Sahebkar (Tabriz University of Medical Sciences, 2016)
Background: Gastro-esophageal reflux disease (GERD) is a common complaint of sulphur mustard (SM)-exposed subjects. Routine treatments such as proton-pump inhibitors (PPIs), H2-blockers and anti-acids cannot control GERD symptoms completely. Aloe vera is a medicinal plant that has been shown to reduce gastric acid secretion. The efficacy of pantoprazole with or without A. Vera juice in alleviating GERD symptoms was investigated in SM-exposed subjects. Methods: Male patients with a history of SM exposure and diagnosed GERD were enrolled and assigned to treatment with pantoprazole (40 mg before breakfast) plus A. vera syrup (5 mL bid before breakfast and at bedtime) (n=44), or pantoprazole alone (40 mg before breakfast) (n=41) for a period of 6 weeks. GERD symptoms were assessed at baseline and weeks 3 and 6 of study using the Reflux Symptom Index (RSI) questionnaire. Results: Seventy-five patients (n=38 and 37 in the A. vera + pantoprazloe and pantoprazole group, respectively) completed the study. No significant difference was found between the groups regarding demographic characteristics and baseline RSI score (p>0.05). A decreasing trend in RSI score was observed in both groups by the 3rd and 6th week of study (p<0.001). There was a greater reduction of RSI score in the A. vera + pantoprazloe versus pantoprazole group (p<0.001). There was no report of any side effects from A. vera during the course of trial. Conclusion: Findings of the present study suggested a significant improvement in the severity of GERD symptoms in SM-exposed subjects following addition of A. Vera to pantoprazole.